Editorial - Guillen, Jorge (2018)
We are proud to present a new issue of the Journal of Economics, Finance and Administrative Science (JEFAS). After editing the special edition of management, this coming corresponds to the December issue, according to our biannual schedule of publication. The first article is “Bank risk and performance in an emerging market setting: the case of Bangladesh”, which investigates the impact of bank capital requirements on the performance and risk of Bangladeshi banking sector. Doi:  https://doi.org/10.1108/JEFAS-11-2018-127